2022
DOI: 10.1021/jacs.2c09785
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic–Morphological Connections in Star Shaped Metal–Organic Frameworks

Abstract: The symmetry of a crystal's morphology usually reflects the symmetry of the crystallographic packing. For single crystals, the space and point groups allow only a limited number of mathematical descriptions of the morphology (forms), all of which are convex polyhedrons. In contrast, concave polyhedrons are a hallmark of twinning and polycrystallinity and are typically inconsistent with single crystallinity. Here we report a new type of structure: a concave polyhedron shape single crystal having a multidomain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
(71 reference statements)
2
5
2
Order By: Relevance
“…We have previously reported stellate and chiral crystals grown from related ligand systems. [66,17] The growth mechanism for the formation of here reported MOFs is completely different than previously reported fullerene flowers. [45] These fascinating cocrystals have multiple decks, the number of which can be controlled by modulating the morphology of the seed crystals.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…We have previously reported stellate and chiral crystals grown from related ligand systems. [66,17] The growth mechanism for the formation of here reported MOFs is completely different than previously reported fullerene flowers. [45] These fascinating cocrystals have multiple decks, the number of which can be controlled by modulating the morphology of the seed crystals.…”
Section: Discussioncontrasting
confidence: 76%
“…[50] We have recently reported on crystallographically related structures having a concave "star"-shaped morphology, and we ruled out the possibility of merohedral twinning as well. [51] A cumulative intensity distribution plot also indicates the formation of noncentrosymmetric, single crystals (Figure S2).…”
Section: Formation and Characterization Of Double-decker Flowers And ...mentioning
confidence: 93%
“…The here observed crystal growth might be general for the formation of analogous systems. The 1.5 h prisms obtained resemble the recently reported "stellate" crystals with re-entrant angles and multidomain morphologies 63 ; however, there are differences in the lateral sides. The reported stellate crystals did not consistently show a medial seam or separation of layers.…”
Section: Mechanism Of the Formation Of Double-decker Flowerssupporting
confidence: 79%
“…49 We have recently reported on crystallographically related structures having a concave "star"shaped morphology, and we ruled out the possibility of merohedral twinning as well. 50 A cumulative intensity distribution plot also indicates the formation of non-centrosymmetric, single crystals (Figure S1).…”
Section: A Formation and Characterization Of Double-decker Flowers An...mentioning
confidence: 93%
“…Chirality is one of the most striking features in nature and it can be observed at all scales, from the molecular structure of amino acids to the spiral structure in distant galaxies. Amazingly, living systems are based almost exclusively on L-amino acids in protein and D-sugars in polysaccharides; this is commonly referred to as biochemical homochirality. From the perspective of chemistry or geochemistry, it has been suggested that inorganic minerals may have played a crucial role in the origin of homochirality in ancient oceans. The natural chiral surfaces of asymmetric or symmetric minerals are considered as an environment where homochirality may have originated. However, it is commonly argued that paired chiral surfaces with equal abundance in nature may not explain the observed global homochirality. Recently, it was found that chiral recognition and separation of chiral amino acids from a mixed racemic state can be achieved by dynamically growing minerals (e.g., calcium carbonate and calcium phosphate crystals) in a nonequilibrium state. The growth mechanism of crystals with chiral morphology or complex structure is also gradually studied. Until now, however, the mechanism of how dynamic crystals selectively recognize chiral enantiomers of organic molecules remained unclear.…”
Section: Introductionmentioning
confidence: 99%